2020
DOI: 10.3906/sag-2004-353
|View full text |Cite
|
Sign up to set email alerts
|

Serum paraoxonase 1 and 3 activities in benign and malignant diseases of the prostate and changes in levels following robotic-assisted laparoscopic radical prostatectomy

Abstract: Background/aim: This study aimed to examine serum paraoxonase 1 and 3 (PON1 and PON3) activities in benign and malignant diseases of the prostate, to determine lipid profile and malondialdehyde (MDA) levels, and to investigate changes in levels following robotic-assisted laparoscopic radical prostatectomy (RALRP).Materials and methods: A total of 137 patients, including a control group, were enrolled in the study and assigned into four groups. Group 1 (n = 33) consisted of patients previously undergoing RALRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Several studies have also reported decreased serum PON1 activity in cancer patients [ 14 ]. While Bedir et al observed lower levels of PON1 in patients diagnosed with PCa, but before treatment, than in healthy population, the exact mechanism involved in the decrease in PON1 activity in PCa patients is still unclear [ 26 ]. In our study, we did not observe such a difference between PCa patients before treatment and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also reported decreased serum PON1 activity in cancer patients [ 14 ]. While Bedir et al observed lower levels of PON1 in patients diagnosed with PCa, but before treatment, than in healthy population, the exact mechanism involved in the decrease in PON1 activity in PCa patients is still unclear [ 26 ]. In our study, we did not observe such a difference between PCa patients before treatment and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of normal levels of the markers of oxidative stress in patients three months after successful RARP suggests that surgical excision of the prostate was associated with the removal of a key source of an excess of free radicals. Despite the fact that the biomarkers studied in the present report lack tissue specificity [ 40 ], these data argue that 8-OHdG and 8-Iso-PGF2α measurements in urine can help to predict radicality (and maybe local recurrence) following PCa surgery. In this study, we used a highly specific and sensitive validated LC–MS/MS method to detect changes in oxidative stress markers in urine samples.…”
Section: Discussionmentioning
confidence: 66%
“…PRRG3 is a protein-coding gene, but to the best of our knowledge, no research has explored its role in cancer. Bedİr et al (2020) found that the PON3 level decreased significantly in patients with PCa. They also found that PON3 increased postoperatively in those with PCa.…”
Section: Discussionmentioning
confidence: 93%
“…They also found that PON3 increased postoperatively in those with PCa. They proposed that surgical excision of malignant tissue in PCa caused a decrease in oxidative stress and that a higher level of PON3 was associated with lower oxidative stress (Bedİr et al, 2020). Finally, IGSF1 is a novel oncogene regulating the progression of thyroid cancer (Guan et al, 2019); however, no study describing its role in PCa has been reported.…”
Section: Discussionmentioning
confidence: 99%